Design and analysis of a portable friction stir welding machine. (2018) - Rohith Renish, R.; Pranesh, M Arun; Logesh, K.
Abstract: Friction stir welding is a mechanism to combine two solid metals without melting. This technique is much preferred for its flexibility, energy efficient, and also environment friendly as it results in high quality welding with low shrinkage. But these machines are giant and also consume more power. In order to address this problem, a portable friction stir welding machine has been designed and analysed. In this study, a machine has been designed to weld plates of 2mm thickness at low power consumption. This could be very much beneficial for the onsite welding processes and also to weld materials of less thickness. The design was done in four stages and the fourth stage was finally analysed for 2 tonne load and the plots are also shown in results and discussion for stress, displacement, strain and factor of safety. The analysis of overall factor of safety of the portable friction stir welding machine shows that all the components are safe except the transverse drive with a Factor of safety 1.431e-001 which is considered to be safe because the applied load is double to that of the required load. The Structural static analysis also was successfully completed using Solid Works by applying 2 tonne load and the results of various parameters such as stress, displacement, strain were plotted and tabulated.